We are given the following succession:
![1+3+5+\cdots+(2n-1)=n^2](https://img.qammunity.org/2023/formulas/mathematics/college/q4aq1rfpydwxc2x82k44x1z0e1r2ksp8dp.png)
To prove this by mathematical induction we need first to determine if the statement is true for n = 1. Replacing we get:
![\begin{gathered} 1=1^2 \\ 1=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dsiq22prd2qlqi69a35fzn197q5facwct3.png)
Therefore, the statement is true for n = 1. Now we will assume that the statement is true and see if it holds for n + 1
Replacing n + 1:
![undefined]()